(untitled) (Global Business Management Review (GBMR), 2019)
The ability of a host country to attract international students depends on many factors, and recommendations or reviews by friends or families who are currently study or had experience studied in a particular host country found to be an effective marketing tool. Based on the data of 753 international students, gathered from a sample of few universities in Malaysia, this study employs a Logit Model in an attempt to identify the factors that affect the decision of the currently enrolled international students to recommend Malaysia to their friends and families as a study abroad destination. The result shows that the university environment, university service, academic quality and social factor affect the decision of the international students to recommend Malaysia. Interestingly, while education cost significantly affects the decision to recommend, it however shows the positive relationship which may suggests that higher cost reflects quality.